The Role of Quality Assurance in Improving the Quality of Education at PKBM Dahlia - Wulan Sari; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the role of quality assurance in improving the quality of education at the Dahlia Community Learning Center (PKBM) in Pekanbaru City. The approach used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that quality assurance is implemented through the stages of planning, implementation, evaluation, and ongoing follow-up. The role of managers and tutors is key to maintaining the quality of learning that is oriented towards the needs of the learners. Quality assurance not only improves learning outcomes but also life skills and independence. However, obstacles remain, such as limited facilities and human resources. Therefore, continuous strengthening of the quality assurance system is necessary to optimize the quality of education at PKBM.